City/Sea Searching for a New Connection. Regeneration Proposal for Naples Waterfront Like an Harbourscape: Comparing Three Case Studies - Russo, Michelangelo; Formato, Enrico (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The port is a strategic area of transition, where it is possible to perceive the territory-landscape and the urban front. However it lost its urban character, gradually becoming an high specialized independent machines, a sectorial infrastructure divided from the city: this phenomenon has created increasingly socio-economical marginalization. Within a double view, lengthwise and transverse, we can describe the port as a space closed to the city and as an unfathomable barrier for the transverse flows that previously connected the waterfront to the city. The paper examines the case study of Naples, where the port expansion continues to grow without any integration with other parts of the city, distorting its “urban area” role, establishing its independence and making urban system compatibility conditions even weaker. The functional and physical division increases the perception of the port as a barrier rather than a filter. Turning the sense of these conditions aims at rethinking waterfront as a public space, a place where integration and specialization spaces become new open and accessible spatial devices. In some contemporary European and American cities (Aalborg, Oslo and Toronto) we could see the port as multifunctional system, an interdisciplinary project that creates urban spaces integrated to the city and that allows the coexistence of different uses. The project of a new public space between the sea and the hinterland could involve all these conflicting functions creating, with different strategies, a potential multifunctional landscape. In Naples as well, where the waterfront is still waiting to be re-connected with the story of the city itself.